Adding which terms to 3x2y would result in a monomial? Check all that apply.3xy–12x2y2x2y27xy2–10x24x2y3x3

Accepted Solution

Answer:[tex]-12x^{2}y[/tex] and [tex]4x^{2}y[/tex]Step-by-step explanation:We are given the term [tex]3x^{2}y[/tex].It is known that, 'A monomial is an algebraic expression consisting of one term'.So, we add the given options to [tex]3x^{2}y[/tex].1.  [tex]3x^{2}y+3xy=3xy(x+1)[/tex]2. [tex]3x^{2}y-12x^{2}y=-9x^{2}y[/tex]3.  [tex]3x^{2}y+2x^{2}y^{2}=x^{2}y(3+2y)[/tex]4.  [tex]3x^{2}y+7xy^{2}=xy(3x+7y)[/tex]5.  [tex]3x^{2}y-10x^{2}=x^{2}(3y-10)[/tex]6.  [tex]3x^{2}y+4x^{2}y=7x^{2}y[/tex]7.  [tex]3x^{2}y+3x^{3}=3x^{2}(y+x)[/tex]As, we can see that only option 2 and 6 results in an expression having one term.Thus, adding [tex]-12x^{2}y[/tex] and [tex]4x^{2}y[/tex] to [tex]3x^{2}y[/tex] results in a monomial.